Review paperAllergic diseases: the price of civilisational progress - Rutkowski, Krzysztof; Sowa, Paweł; Rutkowska-Talipska, Joanna; Sulkowski, Stanisław; Rutkowski, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Atopic disorders are a major global health problem. The prevalence of asthma, allergic rhinitis and atopic dermatitis has been increasing over the last four decades, both in the industrialized and developing countries. It seems to be related to changes in the social structure, increasing industrialization, pollution and dietary changes. Many hypotheses link the allergy epidemic to stringent hygiene, dominance of a westernized lifestyle and an accelerated pace of life. Dietary antioxidants, lipids, sodium, vitamin D seem also to be implicated. We endeavour to review the most relevant theories with a special emphasis on the hygiene, antioxidative, lipid and air pollution hypotheses. It is however important to note that none of them explains all the aspects of unprecedented rise in the prevalence of allergic disorders. A complex interplay between host’s immune response, invading pathogens, diversity of environmental factors and genetic background seems to be of a particular importance. Current allergy epidemic is multifactorial and basic and epidemiologic studies are warranted to further our understanding of this phenomenon.